2005
DOI: 10.1007/s11055-005-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Triphosphate and Ryanodine Receptors in the Control of the Cholinosensitivity of Common Snail Neurons by the Na,K Pump During Habituation

Abstract: The effects of the Na,K pump inhibitor ouabain on habituation of the common snail to tactile stimulation were identical to the ouabain-induced modification of the decrease in the cholinosensitivity of defensive behavior command neurons in the common snail in a cellular model of habituation. Studies addressed the effects of intracellularly delivered ligands of two types of Ca2+ depot receptors--inositol triphosphate (IP3) receptors and ryanodine receptors--on the action of ouabain in the cellular analog of habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[5] This is associated with decreased release of neurotransmitter from the presynaptic terminal because of decreased intracellular Ca 2+ . [16] The decrease in intracellular Ca 2+ is owing to a gradual inactivation of Ca 2+ channels. It can be short-term or it can be prolonged if exposure to the benign stimulus is repeated many times.…”
Section: Discussionmentioning
confidence: 99%
“…[5] This is associated with decreased release of neurotransmitter from the presynaptic terminal because of decreased intracellular Ca 2+ . [16] The decrease in intracellular Ca 2+ is owing to a gradual inactivation of Ca 2+ channels. It can be short-term or it can be prolonged if exposure to the benign stimulus is repeated many times.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated rhythmic tactile stimulation of land snails (Helix lucorum) has caused a weakening of a defensive reaction (Moskvitin and Pivovarov 2004;Nistratova and Pivovarov 2004). Repeated applications of acetylcholine (ACh) to the command neurons of H. lucorum lead to a short-term depression of an acetylcholine-induced inward current (ACh-current).…”
Section: Introductionmentioning
confidence: 99%
“…Local application of constant-size portions of acetylcholine (ACh) to the body surface from an injection micropipette, operating as an artificial presynapse substituting for a presynaptic terminal, results in stable stimulation of a zone of the membrane containing extrasynaptic cholinoreceptors. The stimulation protocol for extrasynaptic cholinoreceptors imitates the stimulation scheme inducing habituation of the animal's defensive reactions [5]. Rhythmic application of ACh in these conditions leads to reversible depression of the evoked influx current (the ACh current), which reflects a decrease in the ACh sensitivity of the membrane [5].…”
mentioning
confidence: 99%
“…The stimulation protocol for extrasynaptic cholinoreceptors imitates the stimulation scheme inducing habituation of the animal's defensive reactions [5]. Rhythmic application of ACh in these conditions leads to reversible depression of the evoked influx current (the ACh current), which reflects a decrease in the ACh sensitivity of the membrane [5].We have previously demonstrated that depression of the cholinosensitivity of the extrasynaptic zones of defensive behavior command neuron membranes in the common snail in a cellular analog of habituation results from a decrease in the number of membrane cholinoreceptors in the test zone [4]. Transport processes (endocytosis and exocytosis, underlying the internalization and recycling of receptors respectively) mediate these changes on the somatic membranes of neurons, with involvement of cytoskeletal elements, i.e., The involvement of cytoskeletal motor proteins, i.e., myosins, in the molecular mechanism of depression of the acetylcholine sensitivity of defensive behavior command neurons was studied in the common snail.…”
mentioning
confidence: 99%
See 1 more Smart Citation